2016
DOI: 10.1016/j.pmedr.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of emerging tobacco products and nicotine replacement therapy among pregnant women and women planning a pregnancy

Abstract: The increasing availability of emerging non-combusted tobacco products (snus, dissolvables, and electronic nicotine delivery systems or ENDS) may have implications for pregnant women and women of reproductive age. We conducted 15 focus groups to explore how women perceive emerging non-combusted tobacco products and nicotine replacement therapy (NRT) in general, and during pregnancy. Sessions were held in 2013 in four U.S. cities. Participants were 18–40 years old and were pregnant smokers, pregnant quitters, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 5 publications
3
41
1
Order By: Relevance
“…EVPs are perceived as safer than cigarettes, especially during high-risk conditions such as pregnancy (1216). A small study of pregnant women who attended a university’s outpatient clinic found that 43% of participants believed that EVPs were less harmful to a fetus than conventional cigarettes, and 57% believed that EVPs contained nicotine (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EVPs are perceived as safer than cigarettes, especially during high-risk conditions such as pregnancy (1216). A small study of pregnant women who attended a university’s outpatient clinic found that 43% of participants believed that EVPs were less harmful to a fetus than conventional cigarettes, and 57% believed that EVPs contained nicotine (18).…”
Section: Discussionmentioning
confidence: 99%
“…Despite increased use of these products in recent years and the risks of use during pregnancy, little is known about public perceptions about the use of these products, particularly among pregnant women. Some studies found that EVPs were perceived as a safer alternative to smoking cigarettes, including during pregnancy (1216). These studies were small in size and limited to specific populations such as a university-based outpatient clinic.…”
Section: Introductionmentioning
confidence: 99%
“…Nicotine, the dependence‐producing drug in ECIGs, is a toxicant of particular concern for pregnant women, as nicotine is known to harm a fetus (e.g., Bruin, Gerstein, & Holloway, ; England et al, ) some have suggested that no amount of nicotine in pregnancy is safe (CDC, ; Suter, Mastrobattista, Sachs, & Aagaard, ). ECIGs differ dramatically in terms of their nicotine delivery, with some products delivering little to no nicotine (e.g., Farsalinos et al, 2014; Vansickel et al, 2010; Yan & D'Ruiz, 2015), and others delivering as much, or more, than a combustible cigarette (e.g., Ramoa et al, 2016; St. Helen, Havel, Dempsey, Jacob III, & Benowitz, ; Wagner et al, ).…”
Section: Do Ecigs Deliver Nicotine and Other Toxicants?mentioning
confidence: 99%
“…In addition to the two primary themes of ECIGs being safer than cigarettes and ECIGs being smoking cessation aids, researchers have noted additional factors related to ECIG use among pregnant women, including the perceived ability to use ECIGs in otherwise smoke-free areas (England et al, 2016), a lower product cost (Bowker et al, 2018;England et al, 2016), the appeal of various flavors (England et al, 2016;Fallin, Miller, Assef, & Ashford, 2016), especially sweet flavors (Stroud, Papandonatos, Borba, Kehoe, & Scott-Sheldon, 2019), and the lack of awareness of nicotine content in the ECIG liquid (Kahr et al, 2015;Kapaya et al, 2019). Interestingly, women also express a desire for credible information related to ECIG safety, specifically from healthcare providers (Bowker et al, 2018).…”
Section: What Are Pregnant Women's Perceptions About Ecigs?mentioning
confidence: 99%
“…In the last decade, the overall use of cigarettes has declined significantly; however, over 10% of pregnant women still smoke during pregnancy, and there is an increased trend towards using non‐combusted tobacco products (snuff, dissolvable, and electronic nicotine delivery systems) that can deliver nicotine during pregnancy (England et al . , ). Nicotine replacement therapies, e.g.…”
Section: Introductionmentioning
confidence: 99%